ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN BERITA HASIL LIPUTAN WARTAWAN - Nori Sahrun (Universitas Asahan, 2019)
With the development of increasingly sophisticated communication technology today, communication is not only done in the form of voice but also in the form of data. So that was born the technology of the first generation to the 5th generation. In the media of data communication that is needed today is the communication in the form of sending services of text messages, images, sound and video in real time. Basically a web-based service is the best solution to support the performance of journalists in managing news more updated and complementing news in accordance with the journalistic code of ethics in avoiding Hoax news. Thus, every reporter when and wherever he is can send news data by accessing the website through a smartphone. Information or news today is very important, wherever and whenever everyone will need an information / news that is happening. The media to get news now is very much, among others, newspapers, television, radio, internet and others. A lot of information is needed, but information seekers are very limited. This system allows us to balance the need for news with news seekers.